Viability of remanufacturing practice: a strategic decision making framework for Chinese auto-parts companies - Abdulrahman, Muhammad Dan-Asabe; Subramanian, Nachiappan; Liu, Chang; Shu, Chengqi (Elsevier, 2015)
Remanufacturing is a sustainable and proven profitable practice in the western world. Research on remanufacturing practices is relatively unexploited in China, despite being the “global factory” and both the world's largest automobile manufacturer and vehicle market. The increasing amount of automotive output and End-of-Life vehicles (ELVs) in China provides Chinese auto-parts companies with significant potential for environmentally conscious manufacturing and product recovery. Using case studies, we have investigated the status of remanufacturing practices, key determinants for strategic decision making to remanufacture in-house, outsource remanufacturing and/or not to engage in remanufacturing in Chinese auto parts firms using an analytical hierarchy process (AHP). This study suggests that Chinese firms are keen to adopt remanufacturing practice in-house compared to outsourcing despite a lack of technical and managerial capabilities.